2021
DOI: 10.4103/aja.aja_7_21
|View full text |Cite
|
Sign up to set email alerts
|

Serum amyloid P component

Abstract: Serum amyloid P component (SAP) is present in seminal plasma, on spermatozoa, and in different tissues of the male reproductive tract, but its function is not known. The aims of this study were to determine if the concentration of SAP in seminal plasma is associated with commonly assessed semen parameters and to investigate if SAP could be a new, indirect biomarker for these parameters. In a cross-sectional study of 203 young volunteers, the concentration of SAP in seminal plasma was measured with a in-house d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Substantial evidence indicates the role of amyloid fibers in various reproductive processes, including gametogenesis, sperm maturation, and fertilization . A recent study by Sonesson et al confirmed the presence of serum amyloid p component and its correlation with sperm concentration . Downregulation of serum amyloid p component (SAMP) in recovered patients indicates the disruption of amyloid fiber formation and crucial reproductive processes due to SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Substantial evidence indicates the role of amyloid fibers in various reproductive processes, including gametogenesis, sperm maturation, and fertilization . A recent study by Sonesson et al confirmed the presence of serum amyloid p component and its correlation with sperm concentration . Downregulation of serum amyloid p component (SAMP) in recovered patients indicates the disruption of amyloid fiber formation and crucial reproductive processes due to SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 99%
“…56 confirmed the presence of serum amyloid p component and its correlation with sperm concentration. 57 Downregulation of serum amyloid p component (SAMP) in recovered patients indicates the disruption of amyloid fiber formation and crucial reproductive processes due to SARS-CoV-2 infection. Besides, pathways such as glycosylation, regulated exocytosis, vesiclemediated transport, and membrane protein proteolysis, which are essential biological processes for fertilization, are also dysregulated in COVID-19-recovered patients.…”
Section: Acsmentioning
confidence: 99%
“…SAP is also a protein of seminal plasma located on sperm flagellum and the tissues of testes and epididymides. Its concentration in seminal plasma correlates with spermiogram parameters [44].…”
mentioning
confidence: 99%
“…These findings are in agreement with previous studies reporting a correlation between APCS and sperm motility and count in seminal plasma. Previous studies also suggested that APCS may be used as a biomarker for low sperm concentrations [ 44 ]. APCS is localized on the surface of mature sperm specifically in the tail of spermatozoa and plays a physiological role in reproduction, more precisely in tail-associated functions such as sperm motility [ 45 ].…”
Section: Discussionmentioning
confidence: 99%